Ortaokul Öğrencilerinin Epistemolojik İnançlarının Keşfedilmesinde Öğrenci Merkezli Bir Yaklaşım: Çiz-Yaz-Anlat Tekniği / A Student-Centered Approach to Explore Middle School Students’ Epistemological Beliefs: Draw-Write-Tell Technique - Üztemur, Servet; Dinç, Erkan (Journal of History Culture and Art Research, 2018)
Abstract The purpose of this research is to explore the epistemological beliefs of middle school students by means of draw-write-tell technique which is formed from three phases. Designed as a qualitative phenomenological research, this study employs 96 students (51 female, 45 male) selected by convenience sampling technique. The participants were attending various grade levels of a state secondary school in Yunusemre district of Manisa province in 2017-2018 academic year. In the first stage of the research, students were asked to pencil draw five things reminding or representing them the word “knowledge”. In the second stage, each student was asked to select one drawing amongst five, which best meets the concept of “knowledge” according to her/his personal opinion and which is identified with “knowledge” the most and write down why she/he chose this one. In the third stage, a total of 12 different focus group interviews were conducted with 53 volunteering students amongst the ones having participated in the earlier research stages. The data obtained from the first stage was thematically analyzed, while the remaining data was analyzed phenomenologically. Research findings show that most of the students see the authorities and the objects out there as sources of knowledge. In the processes of knowledge acquisition, they also perceive themselves as passive recipients of any given knowledge. It is observed that it is possible to measure the epistemological beliefs of the students for the source of knowledge through the drawings and the accuracy and justification of knowledge through the written materials and focus group interviews. Research results show that draw-write-tell technique is a new approach useful and practical in measuring the epistemological beliefs of middle school students. Öz Bu araştırmanın amacı ortaokul öğrencilerinin epistemolojik inançlarını üç aşamadan oluşan çiz-yaz-anlat tekniğiyle keşfetmektir. Nitel araştırma temelinde fenomenoloji modeline göre desenlenen araştırmanın çalışma grubunu 2017-2018 öğretim yılında Manisa ili Yunusemre ilçesindeki bir devlet ortaokulunun kolay ulaşılabilir durum örneklemesi yöntemiyle her sınıf seviyesinden seçilmiş 96 öğrenci (51 kız, 45 erkek) oluşturmaktadır. Araştırmanın birinci aşamasında öğrencilere bilgi deyince akıllarına gelen beş farklı çizim (karakalem) yapmaları istenmiştir. İkinci aşamada öğrencilere bu beş çizim içerisinden kişisel görüşlerine göre bilgi kavramını en çok karşılayan ve bilgi ile en çok özdeşleşen bir tanesini seçip bu çizimi niçin seçtiklerini yazmaları istenmiştir. Üçüncü aşamada katılımcılar içerisinden gönüllülük esasına göre belirlenen 53 öğrenciyle toplam 12 odak grup görüşmesi yapılarak öğrencilerin yazdıkları metinleri daha ayrıntılı bir şekilde ifade etmeleri sağlanmıştır. Birinci aşamadan elde edilen veriler içerik olarak; ikinci ve üçüncü aşamada elde edilen veriler ise fenomenolojik olarak analiz edilmiştir. Araştırma bulguları; öğrencilerin büyük bir kısmının uzmanlar ve dış dünyadaki nesneleri bilginin kaynağı olarak gördüklerini ve bilgi edinme sürecinde kendilerini birer pasif bilgi alıcısı olarak algıladıklarını göstermiştir. Çizimler aracılığıyla öğrencilerin bilginin kaynağına yönelik; yazılı metinler ve odak grup görüşmeleriyle de bilginin kesinliği ve doğrulanması boyutuna yönelik epistemolojik inançlarının tespit edilebildiği görülmüştür. Araştırma sonuçları; yeni bir yaklaşım olan çiz-yaz-anlat tekniğinin ortaokul öğrencilerinin epistemolojik inançlarının ölçülmesinde faydalı ve kullanışlı olduğunu göstermiştir.